Kegiatan Apresiasi Karya Seni Rupa Untuk Meningkatkan Kemampuan Bahasa Anak Usia 5-6 Tahun Di TK Riyadlul Falaah - Pratiwi, Shelly; Zakiah, Rahmy Ainun (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
This research was motivated by problems in children's language abilities. Language skills in early childhood are being able to listen, communicate verbally, have a vocabulary and recognize the symbols that represent them in preparation for reading and writing. So researchers observe that there is a gap between children whose language skills have not yet developed, factors that influence the lack of language development in children are a lack of attention, encouragement and motivation from parents and the environment. This problem occurred in group B at TK RIYADLUL FALAAH, among them the children had not been able to present their work, had not dared to appear in front of friends, and had not dared to express their opinions. This research aims to: 1) Describe the language development of group B children at TK RIYADLUL FALAAH. 2) Describe the activity of appreciating works of fine art in order to develop children's language development at TK RIYADLUL FALAAH  in class B. 3) Describe the language development of children in group B at RA Miftahul Hidayah after the activity of appreciating works of fine art was carried out. The method taken is the classroom action research (PTK) method using the Kemmis MC and Taggart model, with a qualitative approach. Data collection takes the form of interviews, observation and documentation. The results of the research were carried out in 2 cycles with 2 meetings in each cycle, pre-cycle average score 36 with a completion percentage of 47.06%, in the first cycle the average score was 41.5 with a completion percentage of 58.83% from 17 children. Meanwhile, in cycle II the average score was 52 with a completion percentage of 94.12% from 17 children. This shows that there was an increase in the average value of children's language development from cycle I to cycle II.  Keywords: Appreciation, Language Development